Roland Barthes's Secret Garden - Frances Bartkowski (Studies in 20th & 21st Century Literature, 1981)
This article traces the metaphor of the body through all of Barthes's works in order to clarify a further view of Barthes as writer, critic, and reader. Though it is only disclosed in his autobiography as the «manaword» of his vocabulary, it appears as early as Writing Degree Zero in a discussion of 'style' as the literary element that Barthes cannot easily describe or define. The indescribability of style will later be located in such notions as the writerly text, the text of bliss, the unsayable, the disreal. It is the body, the flesh, the idiosyncratic which hides within these categories which elude Barthes, the systematizer of the early structuralist years. Yet in his later works this unnameable aspect of literariness and narrative structure becomes the locus of fascination for Barthes as reader. Through the work of language the Imaginary still speaks, but resists translation into easily serviceable theoretical fictions. In The Lover's Discourse the morality of Barthes's entire project of reading and criticizing narrative is transformed into a desire not to seize at meaning, interpretation or translation. It is through a discussion of the three gardens of his childhood home that one can recreate the itinerary of Barthes slowly passing from easily formalized structures to those that increasingly resist formalism, and his own pleasure in letting go of the wish to read form into that which may not be tamed.
Keywords: metaphor; body; Roland Barthes; writer; critic; reader; autobiography; manaword; Writing Degree Zero; style; The Lover' s Discourse; morality